PENGARUH KUALITAS PELAYANAN TRANSPORTASI ONLINE PT. GOJEK INDONESIA TERHADAP KEPUASAN PELANGGAN PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS TRIDINANTI PALEMBANG - Dwi Karsasih; Sri Murniati (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
This research aims to understand the influence of the quality of services offered by pt.Gojek indonesia towards customer satisfaction among student Majoring in Management Faculty of Economics University Tridinanti palembang with the number of respondents as many as 82 students (of the 100 respondets sampled) in described according to sex, course of study, the first half, and the days of.This research using two variables, namely variable the quality of service as variable independent ( freely with use of five indicators research, that is evidence of display ( tangibles ), the best thing of ( reability ), responsiveness ( responsiveness ), guarantee ( assurance ), danempati ( emphaty ). The regression equation is to research this is y = 31,786 + 0,672x.Based on the results of the analysis simple correlation obtained correlation namely 0,641 which means happened relationships and to relationships that are positive because the value of r positive. While based on the results of index determination, the percentage influence the quality of service for customer satisfaction of 41,1% which means showed a very strong. Keywords : Service Quality, Consumers Satisfaction